(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
In 402 A.D. Claudian declaimed in Rome his poem De bello Getico, praising Stilicho shortly after his controversial victory over Alarich at Pollentia. The poem was recited in front of members of the senatorial aristocracy not necessarily well disposed to Stilicho. Focusing on two specific passages the paper examines how Claudian tried to portray him in a favourable light and to justify his actions, playing with mythological synkrisis and cleverly evoking historical memories and traditions well suited to the audience.